Hegemonía, cultura y educación : Introducción a las Estructuras Culturales Disipativas - Pulido Ch., Orlando (Pulido Chaves) (CLACSO, 2021)
Historically it has not been easy to belong to something, to be someone; Achieving it depends on the confluence of multiple circumstances and factors in scenarios of conflict and tension. Understanding this complexity has been, on the other hand, an ongoing task of anthropology, increasingly shared with other scientific disciplines that see their borders blur every day. Therefore, this text is a pretext, use the expression, to reflect on an anthropology that allows to advance some explanations related to the configuration of the cultural structures that guide the ways of living that generate these shocks, uncertainties, fears and dissatisfactions. Ultimately, it is, neither more nor less, trying to regain confidence in the human being.